Parasitoids (Hymenoptera) of leaf-spinning moths (Lepidoptera) feeding on Vaccinium uliginosum L. along an ecological gradient in central European peat bogs - Lozan, Aurel; Spitzer, Karel; Jaroš, Josef; Khalaim, Andrey; Rizzo, Maria; Guerrieri, Emilio; Bezděk, Aleš (Entomologica Fennica, 2011)
Parasitoids of leaf-spinning Lepidoptera associated with two isolated central European peat bogs were investigated. Five families of parasitoid Hymenoptera (Braconidae, lchneumonidae, Eulophidae, Pteromalidae and Encyrtidae) were recorded. Three categories were recognised: (1) primary parasitoids, (2) facultative hyperparasitoids and (3) obligatory hyperparasitoids. Ten species of Braconidae, five species and seven marked morphospecies among lchneumonidae, and three species of Chalcidoidea were identified. Despite of some niche-specific (but less host-specific) parasitoids, all these hymenopterans are likely to be generalists and none of them were confirmed to be habitat and/or host specialists. Unlike their eurytopic (opportunistic tyrphoneutral) parasitoids, the Lepidoptera hosts associated with peat bogs are partially highly stenotopic (tyrphobionts and tyrphophiles). The occurrence of parasitoids compared to their potential hosts was structured along an ecological (mesoclimatic) gradient, so most parasitoids were recorded from margins while stenotopic (narrow habitat adaptation) moths were mostly distributed near the centre of the bog habitat.